Barriers to cardiac rehabilitation delivery in a low-resource setting from the perspective of healthcare administrators, rehabilitation providers, and cardiac patients - Thaianne Cavalcante Sérvio; Raquel Rodrigues Britto; Gabriela Lima de Melo Ghisi; Lilian Pinto da Silva; Luciana Duarte Novais Silva; Márcia Maria Oliveira Lima; Danielle Aparecida Gomes Pereira; Sherry L. Grace (BMC, 2019)
Abstract Background Despite clinical practice guideline recommendations that cardiovascular disease patients participate, cardiac rehabilitation (CR) programs are highly unavailable and underutilized. This is particularly true in low-resource settings, where the epidemic is at its' worst. The reasons are complex, and include health system, program and patient-level barriers. This is the first study to assess barriers at all these levels concurrently, and to do so in a low-resource setting. Methods In this cross-sectional study, data from three cohorts (healthcare administrators, CR coordinators and patients) were triangulated. Healthcare administrators from all institutions offering cardiac services, and providers from all CR programs in public and private institutions of Minas Gerais state, Brazil were invited to complete a questionnaire. Patients from a random subsample of 12 outpatient cardiac clinics and 11 CR programs in these institutions completed the CR Barriers Scale. Results Thirty-two (35.2%) healthcare administrators, 16 (28.6%) CR providers and 805 cardiac patients (305 [37.9%] attending CR) consented to participate. Administrators recognized the importance of CR, but also the lack of resources to deliver it; CR providers noted referral is lacking. Patients who were not enrolled in CR reported significantly greater barriers related to comorbidities/functional status, perceived need, personal/family issues and access than enrollees, and enrollees reported travel/work conflicts as greater barriers than non-enrollees (all p < 0.01). Conclusions The inter-relationship among barriers at each level is evident; without resources to offer more programs, there are no programs to which physicians can refer (and hence inform and encourage patients to attend), and patients will continue to have barriers related to distance, cost and transport. Advocacy for services is needed.